Gene therapy for respiratory diseases; progress and a changing context - Alton, EWFW; Boyd, AC; Davies, JC; Griesenbach, U; Gill, DR; Harman, TE; Hyde, SC; McLachlan, G (Mary Ann Liebert, 2020)
The UK Respiratory Gene Therapy Consortium (GTC) The GTC was formed in 2001 from three groups at the Universities of Edinburgh and Oxford and Imperial College, London to explore gene therapy as a therapeutic option for people with cystic fibrosis (CF)1. The gene responsible for CF, Cystic Fibrosis Transmembrane conductance Regulator (CFTR), was identified in 19892 and over 2000 mutations are now known3, typically classified into six groups4. Whilst considerable progress has been made with this mutation-agnostic approach, gene therapy is not yet a clinical reality. In parallel, mutation-specific, small molecule CFTR modulator therapy has now demonstrated substantial clinical efficacy5. Here, we briefly summarise the opinions of the GTC on navigating this evolving terrain, as well as noting some opportunities for gene therapy in other respiratory diseases.